Islamic Financial Inclusion and Economic Growth: Empirical Evidence from Indonesia - Ichsan Hamidi; Arip Hidayatul Fadillah; Abdul Bashir; Agung Saputra; Waldi Novi Yarsah (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze the impact of Islamic financial inclusion on economic growth in Indonesia for the period 2018-2022. The research method uses a quantitative approach by utilizing secondary data per province in Indonesia, which is a combination of time series and cross-section (Panel Data) obtained from the OJK and BPS websites. Data analysis was conducted using multiple linear regression analysis using Eviews 10 software. The results of the analysis show that simultaneously, Islamic financial inclusion has a significant impact on economic growth. Furthermore, partially, it was found that third-party funds and Islamic bank financing contributed positively to economic growth. Meanwhile, Islamic financial access shows a negative impact on economic growth in Indonesia for the period 2018-2022.